Analisis pengaruh dana alokasi khusus, dana alokasi umum dan pendapatan asli daerah terhadap indeks pembangunan manusia di Sumatera Utara - Heniwati Gulo; Fitrawaty Fitrawaty; Arwansyah Arwansyah (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
IPM (The Human Development Index) is an indicator in measuring the level of success in improving the quality of human life and determining the rank/level of development of a region. Increasing human resources is also interpreted as increasing the basic capabilities of the population, therefore increasing opportunities to be able to participate in the human development process which requires several basic indices such as spending, education, and health. How is the allocation of regional revenues (Special Allocation Funds, General Allocation Funds, and Local Own Revenue) in the success of human development in matters of infrastructure, health, and education which is one of the important roles of regional regulations in efforts to increase human development. This research was conducted with the aim of knowing